Fear and behavior of young pheasants reared with or without parent figure - Santilli, Francesco; Bagliacca, Marco (Avian biology research, 2019)
Modern game birds rearing methods use mechanical incubators to hatch eggs and artificial brooders to intensively rear birds. However, the lack of parental care can have consequences on behavior and welfare of these birds affecting also survival after their release in the wild. In this study, we compared the response of 4-week-old young pheasants (brooded by a foster mother hen and artificially brooded) to two behavioral tests (duration of tonic immobility and response to aerial predator). Tonic immobility was significantly different between the two groups of birds indicating a higher level of fear in artificially brooded pheasants compared to brooded pheasants. Pheasants brooded by a foster hen showed a stronger response to aerial predator compared to artificially brooded pheasants. The foster hen seems to have a positive effect on pheasant chicks’ behavior reducing the fear and improving the ability to perceive threats.